Graphene and zinc borate reinforced nanocomposites of recycled polypropylene: mechanical, tribological and dynamic mechanical properties - Eker, Beril; Bakbak, Okan; Birkan, Besim Emre; Tasdemir, Munir (SPRINGER, 2026)
Recycled polypropylene (RPP)-based nanocomposites reinforced with graphene (GNP) and/or zinc borate (ZB) were prepared with two different weight fractions (0.5 and 1). This study focused on RPP-based hybrid nanocomposites containing both GNP and ZB reinforcements, investigating their mechanical, thermal, and tribological properties. The hybrid nanocomposites were produced via twin-screw extrusion and injection moulding. Mechanical properties were evaluated through tensile, hardness, and Izod impact tests, while dynamic mechanical analysis (DMA) was performed to examine the storage modulus. Abrasion and friction tests were also conducted to assess tribological behaviour. Incorporation of ZB into RPP improved the elastic modulus by up to 62%, while yield strength increased by 10% compared to pure RPP. Slight enhancements in hardness and impact strength were also observed. Hybrid RPP-GNP-ZB nanocomposites exhibited higher stiffness and improved post-yielding behaviour than single-reinforced and pure RPP samples. DMA results indicated that GNP has a more pronounced effect on the storage modulus than ZB, and hybrid nanocomposites maintained improved thermo-mechanical performance up to 120 degrees C. Tribological tests demonstrated that higher reinforcement contents were associated with increased wear rates. Static and dynamic friction coefficients increased slightly with ZB and more notably with GNP. According to these findings, GNP and ZB reinforcements in recycled polypropylene measurably enhance mechanical and dynamic mechanical properties, highlighting the potential for high-performance polymer applications.
Keywords: Recycled polypropylene; Graphene; Zinc borate; Mechanical properties; Tribological properties; Dynamic mechanical properties; TENSILE PROPERTIES; CARBON NANOTUBE; RETARDANCY; Polymer Science